Dry frictional contact of metal asperities: A dislocation dynamics analysis. (1st May 2016) - Sun, Fengwei; van der Giessen, Erik; Nicola, Lucia
Abstract: Discrete dislocation plasticity simulations are performed to investigate the static frictional behavior of a metal asperity on a large single crystal, in contact with a rigid platen. The focus of this study is on understanding the relative importance of contact slip opposed to plasticity in a single asperity at the micrometer size scale, where plasticity is size dependent. Slip of a contact point is taken to occur when the shear traction exceeds the normal traction at that point times a microscopic friction coefficient. Plasticity initiates through the nucleation of dislocations from Frank-Read sources in the metal and is modeled as the collective motion of edge dislocations. Results show that plasticity can delay or even suppress full slip of the contact. This generally happens when the friction coefficient is large. However, if the flattening depth is sufficiently large to induce nucleation of a large dislocation density, slip is suppressed even when the friction coefficient is very small. This study also shows that when self-similar asperities of different size are flattened to the same depth and subsequently loaded tangentially, their frictional behavior appears size independent. However, when they are submitted to the same contact pressure, smaller asperities slip while larger asperities deform plastically. Graphical abstract: